Elastic or inelastic compression in patients with leg ulcer and restricted mobility? (Veins and Lymphatics, 2013)
In patients with leg ulcer and restricted mobility, compression with elastic material is often preferred based on the concept that it is more effective as it exerts a sustained higher resting pressure while inelastic material is believed to exert a very low resting pressure and to work only during movement. The aim of this study is to demonstrate that elastic and inelastic material can exert similar pressure at rest and that inelastic material can produce a much higher pressure during sitting and light exercise in ulcer patients with restricted mobility. In 30 patients (12 men, 18 women mean age 76.3±9.1 years, range 63-80) with leg ulcers and severely reduced mobility we applied consecutively elastic and inelastic bandages with the same resting pressure of 40 mmHg. Pressure changes were measured while the patient was sitting and standing and during active and passive muscle contractions. The pressure differences between standing and supine and sitting and supine position were calculated as well as between muscle systole and diastole during active and passive contractions. Starting with the same resting pressure inelastic bandages produce significantly higher pressure peaks in the sitting and standing position and during the muscular systole both during active and passive exercise compared to elastic bandages (P
Keywords: elastic compression; inelastic compression; leg ulcers; reduced mobility; immobility.